Simulation Analysis of the Effect of Pile Spacing on the Compressive Load-Bearing Performance of CEP Double Piles - Yongmei Qian; Xun Li; Lishuang Ai; Yaling Jiang; Yu Dong (Advances in Civil Engineering)
Under the action of vertical pressure, the variation of pile spacing affects the bearing performance of concrete expanded-plate (CEP) double pile and the damaged state of soil around the pile. In this study, finite element simulation analysis is performed by ANSYS software, and six sets of semisectional double pile models with different pile spacings and one set of semisectional monopile models with the same specifications are established after applying the vertical pressure to the model pile. The mapping method is used for the pile-soil model meshing, the model adopts the contact type of rigid and flexible bodies, and the simulation analysis adopts the way of applying surface load and loading step-by-step. The displacement distribution, load-displacement curve, stress cloud, and shear stress curve are collated to obtain the displacement and stress change law of pile-soil under different pile spacings and then determine the effect of the changes in pile spacing on the CEP double pile. Meanwhile, the CEP double pile model is compared with the monopile model to determine their similarities and differences. Finally, a reasonable range of pile spacing for CEP double piles is provided. It further improves the research theory of CEP group pile compressive load-bearing capacity and provides the theoretical basis for its design and application in practical engineering.